RELATIONSHIP RELATIONSHIP OF NUTRITIONAL STATUS, ENERGY INTAKE AND WORK ACTIVITIES TOWARDS WORK FATIGUE OF EMPLOYEES AT NUTRITIONAL INSTALLATIONS OF AWAL BROS HOSPITAL PEKANBARU 2020: Hubungan Status Gizi, Asupan Energi Dan Aktivitas Fisik Terhadap Kelelahan Kerja Pada Karyawan Instalasi Gizi Rumah Sakit Awal Bros Pekanbaru - yola daswin; Novita Rani; Sri Desfita (Progam Studi Kesehatan Masyarakat STIKes Hang Tuah Pekanbaru, 2021)
ABSTRACT Work fatigue is a mental or physical fatigue that reduces a person's ability to do a job safely and effectively. At this time, health and nutrition are important factors that affect the quality of human resources (HR). The purpose of this study was to determine the relationship between nutritional status, energy intake and physical activity on fatigue in nutrition installation employees at Awal Bros Hospital Pekanbaru 2020. This type of research is quantitative analytic with cross sectional design. The population of this study were all Nutrition Installation employees at Awal Bros Hospital in Pekanbaru were 50 people. The sampling technique used was total sampling. Types of data are primary and secondary data. Data analysis was performed univariate and bivariate using chi square. Based on the results of the study, it is known that most of them have abnormal nutritional status as many as 35 people (70%) and most of them have bad energy intake as many as 31 people (62%). Most of the respondents had bad physical activity as many as 27 people (54%). Most of the respondents felt tired as many as 32 people (64%). The conclusion of this research is there is a relationship between nutritional status (p value = 0.008), energy intake (p value = 0.005) and physical activity (p value = 0.002) with fatigue at Awal Bros Hospital, Pekanbaru 2020. Advice to workers to pay more attention to nutritional status and energy intake so as not to cause excessive work fatigue. Regarding physical activity factors, hospitals need to pay attention to rest periods, workplace conditions, burdens and assistive devices used so that fatigue does not lead to workplace accidents.